Executive functions in adults born small for gestational age at term: a prospective cohort study - Mariell Nordgård; Martine Reitan Udnæs; Kristina Anna Djupvik Aakvik; Silje Dahl Benum; Sigrid Hegna Ingvaldsen; Siri Weider; Kari Anne I. Evensen (Scientific Reports)
Abstract There are mixed findings regarding executive functioning in individuals born small for gestational age (SGA) at term and associations between performance-based and self-reported executive functions have yet to be examined in adults. In a prospective cohort study, 56 SGA and 68 non-SGA control participants were assessed at 32 years using the performance-based Trail Making Test (TMT) and the self-report questionnaire Behavior Rating Inventory of Executive Function – Adult Version (BRIEF-A). The SGA group used 1.6 (95% confidence interval [CI] 0.1–3.1) to 3.9 (95% CI 1.2–6.5) seconds more on TMT conditions 1 and 3, indicating more difficulties with visual scanning and letter sequencing than controls. On BRIEF-A, the SGA group scored 1.5 (95% CI 0.2–2.8) points lower on the clinical scale Emotional Control. Correlation coefficients for the association between TMT and BRIEF-A scores ranged from -0.295 (p = 0.065) to 0.345 (p = 0.029) in the SGA group. In conclusion, we found that 32-year-old adults born SGA at term showed poorer performance on some executive function tasks than controls. However, they reported similar executive functioning in everyday life, except for emotional control. The associations between performance-based and self-report assessments of executive functions were weak.